Corrective Feedbacks and Grammar Teaching in a Situated Teaching Context of Process-Based Writing - Hartono, Hartono; Anwar, Choiril; Murtiningrum, Afina (Register Journal, 2019)
This study was aimed at finding out 1) how learners in a specific teaching-learning context namely process-based academic essay writing perceived the importance of corrective feedbacks (CF); 2) what CF was expected the most; 3) in what way learners preferred to have their CF  provided; and 4) how learners perceived the importance of grammar teaching. It was conducted at English Literature Department of a university in Central Java Indonesia. Forty two students who were taking Essay Writing course served as the subjects for the study. The course itself was delivered in a process-based writing in which content development and rhetoric were given more emphasis than grammar accuracy was. Data for the study were collected by questionnaire and a semi-structured interview with 5 guided questions. The findings suggest that learners still considered CFs as highly important and useful for their writing improvement. Learners expected to have comprehensive CFs of grammar, vocabulary, spelling, organization and punctuation, and CF on grammar was the most preferred one. In terms of CF provision technique, underlying and making notes were the most preferred techniques. Finally, this study concludes that the shift of approach from a product-based to a process-based did not significantly change learners’ focus from forms to content.